Letter from Georg Bredig to Hugh S. Taylor, December 19, 1939 - Bredig, Georg (1939)
Georg Bredig (1868-1944) informs Hugh S. Taylor (1890-1974) that he will accept the position at Princeton University. Bredig thanks Taylor for his help in obtaining this position and congratulates him on his twenty-five years of service as a university professor.
Keywords: Bredig, Georg, 1868-1944; Taylor, Hugh S. (Hugh Stott), 1890-1974; Emigration and immigration; Princeton University